Association of adverse childhood experiences with menopausal symptoms: Results from the Data Registry on Experiences of Aging, Menopause and Sexuality (DREAMS). (January 2021) - Kapoor, Ekta; Okuno, Madison; Miller, Virginia M.; Rocca, Liliana Gazzuola; Rocca, Walter A.; Kling, Juliana M.; Kuhle, Carol L.; Mara, Kristin C.; Enders, Felicity T.; Faubion, Stephanie S.
Highlights: Adverse experiences in childhood are associated with chronic illness in adulthood. The association of childhood adversity and the menopause experience is not well studied. The study reports an association between childhood adversity and menopause symptoms. The association persisted even after adjustment for multiple confounders. Women with severe menopause symptoms should be screened for childhood adversity. Abstract: Objective: To examine the association of adverse childhood experiences (ACEs) with overall menopausal symptom burden in midlife women. Study design: This was a cross-sectional study of women between the ages of 40 and 65 years who were seen for specialty consultation in the Menopause and Women's Sexual Health Clinic, Mayo Clinic, Rochester, MN between May 1, 2015 and December 31, 2016. Main outcome measures: Participants completed the ACE questionnaire to assess childhood abuse and neglect, the Menopause Rating Scale (MRS) to assess menopausal symptom burden, the Patient Health Questionnaire (PHQ-9) to assess depression, the Generalized Anxiety Disorder questionnaire (GAD-7) to assess anxiety, and provided information on current abuse (physical, sexual and verbal/emotional). Results: Women meeting inclusion criteria (N = 1670) had a median age of 53.7 years (interquartile range: 49.1, 58.0). Of these women, 977 (58.5 %) reported any ACE and 288 (17.2 %) reported ≥4 ACEs. As menopausal symptoms increased in severity from the first to fourth quartile, the odds ratio of ACE 1-3 (vs. 0) increased from 1 to 2.50 (trend p < 0.01), and the odds ratio of ACE ≥ 4 (vs. 0) increased from 1 to 9.61 (trend p < 0.01), a pattern that was consistent across all menopausal symptom domains. The association between severe menopausal symptoms and higher childhood adversity (ACE score 1-3 or ≥4 vs. ACE = 0) remained significant after adjusting for age, partner status, education, employment, depression, anxiety, and hormone therapy use (OR 1.84 and 4.51, p < 0.01). Conclusion: In this large cross-sectional study, there was a significant association between childhood adversity and self-reported menopausal symptoms that persisted even after adjustment for multiple confounders. These associations highlight the importance of screening women with bothersome menopausal symptoms for childhood adversity, and of offering appropriate management and counseling for the adverse experiences, when indicated.